2012
DOI: 10.3354/dao02455
|View full text |Cite
|
Sign up to set email alerts
|

Histological intersex (ovotestis) in the European lobster Homarus gammarus and a commentary on its potential mechanistic basis

Abstract: This paper provides the first report of the intersex (ovotestis) condition in the European lobster Homarus gammarus. A single specimen (10% of males sampled) presenting the condition was discovered as part of routine sampling, from the Weymouth Bay region of the English Channel, UK. The lobster presented externally as a male, but upon histological examination was seen to contain an ovotestis, containing elements of both male and female gonadal tissue. Previtellogenic oocytes were present in several otherwise n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Although the relationship between oestrogenic chemicals and crustacean feminisation is still uncertain, other (non-oestrogenic) chemicals in the environment may cause unambiguous crustacean feminisation. Indeed, chemical contaminants (or mixtures of contaminants) have been implicated as a cause of the intersex phenotypes observed in multiple crustacean groups (Moore and Stevenson, 1994;Jungmann et al, 2004;Ayaki et al, 2005;Short et al 2012a;Stentiford, 2012). However, the finding that obviously female sexual characteristics can appear on males in the absence of any Vtg expression suggests that the aberrant expression of Vtg in males is not suitable as an 'early warning' biomarker, even if there are chemicals that unambiguously feminise crustaceans.…”
Section: Implications For the Use Of Vtg As A Biomarkermentioning
confidence: 99%
“…Although the relationship between oestrogenic chemicals and crustacean feminisation is still uncertain, other (non-oestrogenic) chemicals in the environment may cause unambiguous crustacean feminisation. Indeed, chemical contaminants (or mixtures of contaminants) have been implicated as a cause of the intersex phenotypes observed in multiple crustacean groups (Moore and Stevenson, 1994;Jungmann et al, 2004;Ayaki et al, 2005;Short et al 2012a;Stentiford, 2012). However, the finding that obviously female sexual characteristics can appear on males in the absence of any Vtg expression suggests that the aberrant expression of Vtg in males is not suitable as an 'early warning' biomarker, even if there are chemicals that unambiguously feminise crustaceans.…”
Section: Implications For the Use Of Vtg As A Biomarkermentioning
confidence: 99%
“…Although some parasite-induced intersexuality exists naturally, several authors have shown that crustacean intersexuality was linked to environmental contamination in copepods (Moore and Stevenson, 1991), amphipods (Barbeau and Grecian, 2003;Jungmann et al, 2004;Ford et al, 2006;Yang et al, 2008;Hyne, 2011;Short et al, 2012), and decapods (Sangalang and Jones, 1997;Ayaki et al, 2005;Stentiford, 2012). A proportion of intersexes may be indirectly caused by anthropogenic contamination, as contaminant-exposed crustaceans present significant increases in infection by microsporidia (Short et al, 2014).…”
Section: Reproductive Health: Imposex and Intersexmentioning
confidence: 99%
“…In any case, no prominent example of endocrine disruption, comparable to imposex in prosobranch gastropods, is known for crustaceans. Examples of intersex that appear to be related to pollution have been reported for different crustacean species (14)(15)(16)(17)(18)(19). But no cause-effect relationships have been established.…”
Section: Introductionmentioning
confidence: 99%